2018
DOI: 10.1111/desc.12687
|View full text |Cite
|
Sign up to set email alerts
|

Infants' attention bias to faces as an early marker of social development

Abstract: Infants have a strong tendency to look at faces. We examined individual variations in this attentional bias in 7-month-old infants by using a face-distractor competition paradigm and tested in a longitudinal sample whether these variations were associated with outcomes reflecting social behavior at 24 and 48 months of age (i.e., spontaneous helping, emotion understanding, mentalizing, and callous-unemotional traits; N = 100-138). The results showed a robust and distinct attention bias to faces at 7 months, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
104
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 67 publications
(177 reference statements)
12
104
1
1
Order By: Relevance
“…For example, at only 5 weeks of age, human infants’ greater relative interest in a face compared to a nonsocial object predicts lower levels of callous‐unemotional traits, and greater emotion recognition and empathy, 2.5 years later (Bedford, Pickles, Sharp, Wright, & Hill, 2015). Additionally, greater attention to faces at 7 months predicts children's helping behaviors at 2 years and is associated with reduced callous‐unemotional traits at 4 years of age (Peltola, Yrttiaho, & Leppänen, 2018). Given the importance of social attention, and that early deviations from typical social attention may signify developmental disruptions, there is a need to better understand healthy typical development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at only 5 weeks of age, human infants’ greater relative interest in a face compared to a nonsocial object predicts lower levels of callous‐unemotional traits, and greater emotion recognition and empathy, 2.5 years later (Bedford, Pickles, Sharp, Wright, & Hill, 2015). Additionally, greater attention to faces at 7 months predicts children's helping behaviors at 2 years and is associated with reduced callous‐unemotional traits at 4 years of age (Peltola, Yrttiaho, & Leppänen, 2018). Given the importance of social attention, and that early deviations from typical social attention may signify developmental disruptions, there is a need to better understand healthy typical development.…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial body of literature concerning the 7‐month‐old and older infant bias for viewing fearful faces, but less is known about the mechanisms underlying the bias and the developmental trajectory of looking time preference. Emerging longitudinal studies have provided some information about the attentional bias to faces in the first year of life and later stages of development (Leppänen, Cataldo, Enlow, & Nelson, ; Peltola, Yrttiaho, & Leppänen, ). Some have found the bias for fearful faces holds at 36 months of age (Leppänen et al ., ), and others showed a decline in looking times for fearful faces between seven and 24 months of age (Peltola et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging longitudinal studies have provided some information about the attentional bias to faces in the first year of life and later stages of development (Leppänen, Cataldo, Enlow, & Nelson, ; Peltola, Yrttiaho, & Leppänen, ). Some have found the bias for fearful faces holds at 36 months of age (Leppänen et al ., ), and others showed a decline in looking times for fearful faces between seven and 24 months of age (Peltola et al ., ). Other investigators who examined infants from 4–24 months of age have found that infants spend a greater amount of time attending to emotional faces with age, particularly threatening faces (Pérez‐Edgar et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Affect-biased attention is also evident in later attentional components (Morales et al, 2016), as research using both looking time and eye-tracking measures have demonstrated a bias in disengaging from fearful faces. For example, 7-month-old infants dwell longer on fearful faces than happy faces (Leppänen, Cataldo, Enlow, & Nelson, 2018;Peltola, Yrttiaho, & Leppänen, 2018), and they are slower to look away from fearful versus happy or neutral faces when a neutral stimulus is presented to the left or right of the face (Peltola et al, 2013;Peltola, Leppänen, Palokangas, & Hietanen, 2008;Peltola, Leppänen, Vogel-Farley, Hietanen, & Nelson, 2009). Importantly, the early developmental preparedness for emotional processing might not be specific to fearful or threatening facial expressions (Leppänen, 2011;Leppänen & Nelson, 2009).…”
mentioning
confidence: 99%